2017
DOI: 10.1177/0037549717734633
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of pedestrian flow with evading and surpassing behavior in a walking passageway

Abstract: The pedestrian flow with evading and surpassing behavior in a walking passageway is simulated based on a modified social force model in order to explore the influence of this behavior on evacuation efficiency, bottleneck passing capacity, and the macroscopic phenomenon. A pair of conjugated self-driven forces is introduced to enable a pedestrian to avoid a direct collision and keep a normal velocity magnitude while confronting an obstacle. The pedestrian avoiding time is used to define the triggering condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Pedestrian's avoiding behavior is the main focus of research in path planning's decision level. e original social force model's psychological repulsive force could not show a pedestrian's voluntary avoiding behavior; thus, further research improved social avoiding force's form and mechanism [13][14][15]. For example, Wang et al [16] proposed that pedestrians adjust their desired speed considering the position of exits, obstacles, and other pedestrians to facilitate their discovery of the quickest path to destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pedestrian's avoiding behavior is the main focus of research in path planning's decision level. e original social force model's psychological repulsive force could not show a pedestrian's voluntary avoiding behavior; thus, further research improved social avoiding force's form and mechanism [13][14][15]. For example, Wang et al [16] proposed that pedestrians adjust their desired speed considering the position of exits, obstacles, and other pedestrians to facilitate their discovery of the quickest path to destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another example is the positioning of suitably placed objects—for instance, a number of pillars—at the exits from places usually left by large flows of people: for instance, sports stadiums. It has been shown that this apparently counterintuitive strategy accelerates the flow of people away from collective places of this kind (Jiang et al., 2014; Jia et al., 2017; Zhao et al., 2017). Yet another example is represented by black silhouettes in the shape of a person used along particularly hazardous roads to mark the place where someone has lost his/her life in a road accident: the purpose being to prompt motorists to drive carefully (Tromp et al., 2011).…”
Section: Three Dimensions Of Rule‐free Regulation: Teleological Techn...mentioning
confidence: 99%
“…We first listed the self-motivated individual motion behaviors including overtaking [15], evading [40], following [41], and self-slowing [16], as well as the crowd motion behaviors, i.e., queuing [17] and grouping [42]. Then, we categorized 10 types of self-organization phenomena including herding [43], bubble effect [44], lane formation [45], stripe formation [9], zipper effect [20], oscillatory flow [46], faster-is-slower [5], freezing-by-heating [23], stop-go waves [47], and turbulent flow [48].…”
Section: Complex Movements Of Pedestrian Flowmentioning
confidence: 99%